Moments of Being: Carol Shields’s Short Fiction - D’hoker, Elke (Studies in Canadian Literature, 2008)
Carol Shields’s short fiction eschews the teleological model of plot development, and instead develops coherence through associations, thematic development, and epiphanies — what Virginia Woolf calls "moments of being." Shields departs from modernist short fiction by transforming the literary moment so that it becomes a part of both the experimental structure and world view of her stories. In so doing, she departs from the modern Joycean epiphanic tradition, as expounded by theorists such as Morris Beja, Ashton Nichols and Robert Langbaum. Unlike epiphanies in the Joycean tradition, Shields’s foreground experience over insight, and they emphasize the embeddedness of the epiphany in the domestic, in keeping with what Martin Hiedegger calls "residency."